Development and implementation of guidelines for quality assurance in breast cancer screening: The European experience. - Lawrence von Karsa; Silvina Arrossi (Instituto Nacional de Salud Pública, 2013)
In Europe, as in many other regions of the world, breast cancer is a major cause of suffering and death. Early detection of breast cancer by systematic mammography screening can find lesions for which treatment is more effective and generally more favourable for quality of life. Comprehensive quality assurance guidelines for breast cancer screening based on mammography have been developed in the Europe Against Cancer programme with the aim of maximising screening benefits while minimising adverse effects, such as unnecessary examination or treatment resulting from false-positive screening tests. The present report provides an overview of the European experience in developing and implementing quality assurance guidelines for breast cancer screening. It highlights implications relevant to those regions of the world in which the burden of breast cancer in the coming years will make population-based screening an option for cancer control.